Infrared welding of cross-linkable polyamide 66 - C. Leisen; D. Drummer (eXPRESS Polymer Letters, 2016)
Radiation cross-linking of polyamide 66 with electron beams alters the material’s characteristics. This leads to a varied relationship amongst the process, structure, and properties for infrared welding cross-linked polyamide 66. A threedimensional network of covalent bonds results in an impeded melt flow and altered welding characteristics. Compared to non-cross linked polyamide, a changed energy input in the weld during infrared heating and a reduced meltdown can be observed. Such thermal developments and a reduced meltdown affect the resulting weld strengths. Welding factors of almost 60% of base material strengths can be achieved. A clear influence of the heating time on the weld strength can be observed. The scope of this article is to investigate the influence of radiation cross-linking on the material characteristics and, by extension, the resulting processing and welding characteristics. Mechanical and optical investigations serve to highlight the influence of radiation cross-linking on the infrared welding process of polyamide 66.